Spatial inter-centromeric interactions facilitated the emergence of evolutionary new centromeres - Guin, Krishnendu (2020)
Centromeres of Candida albicans form on unique and different DNA sequences but a closely related species, Candida tropicalis, possesses homogenized inverted repeat (HIR)-associated centromeres. To investigate the mechanism of centromere type transition, we improved the fragmented genome assembly and constructed a chromosome-level genome assembly of C. tropicalis by employing PacBio sequencing, chromosome conformation capture sequencing (3C-seq), chromoblot, and genetic analysis of engineered aneuploid strains. Further, we analyzed the 3D genome organization using 3C-seq data, which revealed spatial proximity among the centromeres as well as telomeres of seven chromosomes in C. tropicalis. Intriguingly, we observed evidence of inter-centromeric translocations in the common ancestor of C. albicans and C. tropicalis. Identification of putative centromeres in closely related Candida sojae, Candida viswanathii and Candida parapsilosis indicates loss of ancestral HIR-associated centromeres and establishment of evolutionary new centromeres (ENCs) in C. albicans. We propose that spatial proximity of the homologous centromere DNA sequences facilitated karyotype rearrangements and centromere type transitions in human pathogenic yeasts of the CUG-Ser1 clade.